Responses of carbon and oxygen stable isotopes in rice grain (Oryza sativa L.) to an increase in air temperature during grain filling in the Japanese archipelago - Akamatsu, Fumikazu; Suzuki, Yaeko; Nakashita, Rumiko; Korenaga, Takashi (Ecological research, 2014)
Stable isotopic compositions of carbon (δ¹³C) and oxygen (δ¹⁸O) in plants reflect growth conditions. Therefore, these isotopes might be good indicators of changes in environmental factors, such as variations in air temperature caused by climate change. It is predicted that climate change will lead to a greater increase in minimum air temperatures (primarily during the night) than in maximum air temperatures (primarily during the day) in many parts of Japan. In the present study, we investigated whether the δ¹³C and δ¹⁸O of the rice grain Koshihikari (Oryza sativa L.) from the northern latitudes (30.49°–37.14°) of Japan reflect variations in air temperature during grain filling and are related to the yield and proportion of first-grade rice (<15 % transparency, roundness, and cracking) as an indicator of quality. We revealed that rice δ¹³C was not correlated with mean maximum or minimum air temperatures for each prefecture. By contrast, rice δ¹⁸O was positively correlated with mean minimum air temperature, suggesting that rice δ¹⁸O reflects changes in night air temperature. We further showed that an increase in the mean minimum air temperature during grain filling had a negative effect on rice yield and quality. Our findings indicate that the δ¹⁸O of rice grain may be a good indicator of physiological changes in response to minimum air temperatures during grain filling.